Electrophysiological effects of desflurane in children with Wolff‐Parkinson‐White syndrome: a randomized crossover study. Issue 2 (25th October 2017) - Hino, H.; Oda, Y.; Yoshida, Y.; Suzuki, T.; Shimada, M.; Nishikawa, K.
Abstract : Background: We hypothesized that, compared with propofol, desflurane prolongs the antegrade accessory pathway effective refractory period (APERP) in children undergoing radiofrequency catheter ablation for Wolff‐Parkinson‐White (WPW) syndrome. Methods: In this randomized crossover study, children aged 4.1−16.1 years undergoing radiofrequency catheter ablation for WPW syndrome were randomly divided into four groups according to the concentration of desflurane and anesthetics used in the first and the second electrophysiological studies (EPS). After induction of general anesthesia with propofol and tracheal intubation, they received one of the following regimens: 0.5 minimum alveolar concentration (MAC) desflurane (first EPS) and propofol (second EPS) (Des0.5‐Prop group, n  = 8); propofol (first EPS) and 0.5 MAC desflurane (second EPS) (Prop‐Des0.5 group, n  = 9); 1 MAC desflurane (first EPS) and propofol (second EPS) (Des1.0‐Prop group, n  = 10); propofol (first EPS) and 1 MAC desflurane (second EPS) (Prop‐Des1.0 group, n  = 9). Radiofrequency catheter ablation was performed upon completion of EPS. Sample size was determined to detect a difference in the APERP. Results: Desflurane at 1.0 MAC significantly prolonged the APERP compared with propofol, but did not affect the sinoatrial conduction time, atrio‐His interval or atrioventricular node effective refractory period. Supraventricular tachycardia was induced in all children receiving propofol, but not induced in 1 and 4 children receiving 0.5 MAC and 1.0 MAC desflurane, respectively. Conclusion: Desflurane enhances the refractoriness and may block the electrical conduction of the atrioventricular accessory pathway, and is therefore not suitable for use in children undergoing radiofrequency catheter ablation for WPW syndrome.